Acute and subchronic toxicities of the ethanol and hot-water extracts from Chinese sumac (Rhus chinensis Mill.) fruits by oral administration in rats. (September 2018) - Wu, Zihuan; Ma, Yanli; Zhao, Lei; Cai, Shengbao; Cheng, Guiguang
Abstract: In the present work, acute and subchronic toxicities of the ethanol and hot-water extracts from Rhus chinensis Mill. fruits were performed by oral administration in pathogen-free SD rats. Acute toxicity study was performed at a single dose of 5000 mg/kg for 14 consecutive days. And subchronic toxicity test was conducted by daily oral administration of those two extracts at doses of 312, 625, 1250 and 2500 mg/kg for 30 days. Acute toxicity study showed that the LD50 of the ethanol and hot-water extracts were over 5000 mg /kg. The results of subchronic toxicity showed that no significant adverse effect of those two extracts was observed at 312 and 625 mg/kg. However, the weight gains of rats were significantly inhibited at both 2500 mg/kg groups of the ethanol and hot-water extracts. Moreover, those two extracts exhibited toxicities to heart, liver, spleen and kidney in rats determined by hematological, serum biochemical and/or histological analyses when daily oral administration of 1250 mg/kg and 2500 mg/kg. No significant neurotoxicity was observed in all groups. The results concluded that the low concentration of those two extracts from R. chinensis Mill. fruits can be regarded as safe and used in daily life Graphical abstract: Highlights: Acute & subchronic toxicity of 2 extracts from R. chinensis Mill. fruits were studied. The LD50 of both extracts were over 5000 mg/kg evaluated by acute toxicity. Both extracts can be regarded as practically non-toxic based on acute toxicity. Extracts didn't show toxicity at 312 mg/kg and 625 mg/kg by subchronic toxicity. Both extracts showed toxicities to some organs at 1250 mg/kg and 2500 mg/kg.